DESENT: Smart decision support system for urban energy and transportation. - Hummer, Evelyn; Nacht, Thomas; Kolb-Stögerer, Isabella; Yang, Dujuan (My University, 2018)
Das Projekt DESENT zielt auf die Entwicklung, Anwendung und Verbreitung eines Entscheidungstools für den Energieverbrauch von Gebäuden und Verkehr ab, das maximale Effizienz in Bezug auf Energieversorgung und dezentraler Energieerzeugung gewährleistet.

The focus of this paper is on the DESENT project, which aims to develop, test and disseminate a comprehensive decision support system for smart energy and transport in cities. Transport energy consumption modelling, building supply and energy demand tools are combined to provide a common decision support system for appraisal of city-wide energy use. The system will be set up as planning toolbox that consists of several models and tools providing different functionalities to show actual data for energy demand and transport energy demand and furthermore allow to predict the energy demand on building and city level for future planning scenarios. Thus, the relationships between sustainability objectives, transport, spatial design of the built environment and rational use of energy are considered. The paper describes the concept and structure of the planning toolbox and its models and tools developed so far. Furthermore, it outlines methodologies developed and the data acquisition process for the city of Weiz, which serves as one of the pilot cities in the project. Keywords: energy demand prediction, smart city development, transport energy demand, uncertain supply, optimal energy distribution The focus of this paper is on the DESENT project, which aims to develop, test and disseminate a comprehensive decision support system for smart energy and transport in cities. Transport energy consumption modelling, building supply and energy demand tools are combined to provide a common decision support system for appraisal of city-wide energy use. The system will be set up as planning toolbox that consists of several models and tools providing different functionalities to show actual data for energy demand and transport energy demand and furthermore allow to predict the energy demand on building and city level for future planning scenarios. Thus, the relationships between sustainability objectives, transport, spatial design of the built environment and rational use of energy are considered. The paper describes the concept and structure of the planning toolbox and its models and tools developed so far. Furthermore, it outlines methodologies developed and the data acquisition process for the city of Weiz, which serves as one of the pilot cities in the project.
Keywords: Stadtentwicklungsplanung; Energiebedarf; Energieversorgung; Energieplanung; Smart City; Entscheidungsmethode; Berechnungsmethode